2022
DOI: 10.29393/chjaa38-26hdnv10026
|View full text |Cite
|
Sign up to set email alerts
|

PLANT ANALYSIS BASED ON THE DRIS SYSTEM: PROGRAMMING INTERFACE WITH A CASE STUDY IN PLANTAIN CROP (Musa AAB)

Abstract: The Diagnosis and Recommendation Integrated System (DRIS) is a tool to evaluate the nutritional status and obtain fertilizer recommendations of several crops. Unlike other methods, DRIS works directly with farmer’s information, focusing on understanding the nutritional balance of the crop. However, the selection of indexes is long and time-consuming. The objective of this work was to develop an algorithm to estimate reference and DRIS indexes for crops in order to facilitate the use of the DRIS methodology. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…We successfully determined the optimal nutrient range in durian leaf cultivated on the VMD (Table 4). In this study, the proposed nutrients (g kg −1 ) that are optimal for leaf durian are 19.8-26.0 N, 2.11-2.90 P, 17.4-24.6 K, 20.8-32.6 Ca, 3.81-7.30 Mg, and 2.21-4.40 S. These optimum ranges for durian leaves at the stage 2 months before flowering agree with the results of Poovarodom et al [13], who reported the standard concentrations (g kg −1 ) of N (20-24), P (1.5-2.5), K (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), Ca (17)(18)(19)(20)(21)(22)(23)(24)(25), and Mg (2.5-5.0) in durian leaf cultivated in Thailand. Another study [46] in Thailand showed that the average nutrient concentrations (g kg −1 ) in durian leaf were 19-23, 1.7-2.6, 14-18, 20-35, 4.4-6.9, and 2.4-2.7 (N, P, K, Ca, Mg, and S, respectively).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We successfully determined the optimal nutrient range in durian leaf cultivated on the VMD (Table 4). In this study, the proposed nutrients (g kg −1 ) that are optimal for leaf durian are 19.8-26.0 N, 2.11-2.90 P, 17.4-24.6 K, 20.8-32.6 Ca, 3.81-7.30 Mg, and 2.21-4.40 S. These optimum ranges for durian leaves at the stage 2 months before flowering agree with the results of Poovarodom et al [13], who reported the standard concentrations (g kg −1 ) of N (20-24), P (1.5-2.5), K (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), Ca (17)(18)(19)(20)(21)(22)(23)(24)(25), and Mg (2.5-5.0) in durian leaf cultivated in Thailand. Another study [46] in Thailand showed that the average nutrient concentrations (g kg −1 ) in durian leaf were 19-23, 1.7-2.6, 14-18, 20-35, 4.4-6.9, and 2.4-2.7 (N, P, K, Ca, Mg, and S, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…Leaf diagnosis is a complex method because it is affected by foliar age and other interactions, which directly influence nutrient uptake and distribution [14]. Various approaches are utilized to interpret the nutritional status of plants using leaf analysis, such as the identification of deficiency symptoms, determining the ratio of nutrients, or using the diagnosis and recommendation integrated system (DRIS) [17,18]. DRIS was introduced and developed by Beaufils (1957Beaufils ( , 1971Beaufils ( , and 1973) as a solution for tackling the difficulties inherent in diagnostic methods utilizing leaves [19].…”
Section: Introductionmentioning
confidence: 99%
“…The primary sampling material among the several tissues that should be taken into account for nutritional diagnostic purposes is leaves. The development of tissue analysis techniques made it possible to compare the outcomes of various soil-type fertilization trials [7,8] .…”
Section: Introductionmentioning
confidence: 99%